Multiple effects of lcrD mutations in Yersinia pestis. - Plano, G V (1993)
Plasmid pCD1 of Yersinia pestis contains a low-calcium response stimulon responsible for the temperature- and calcium-regulated expression and secretion of proteins involved in virulence, which include the V antigen and Yops. We have previously shown that insertional inactivation of the bicistronic lcrDR operon abolished the calcium requirement for growth at 37 degrees C and reduced expression of the V antigen and Yops. In this study, we constructed and characterized three mutants having nonpolar lcrD deletions. All three mutants lost the two main low-calcium response properties: a calcium requirement for growth at 37 degrees C and strong expression of the V antigen and Yops. The effects on virulence gene expression occurred at both the levels of transcription and secretion. The growth, transcription, and secretion defects could be at least partially complemented for two of the lcrD mutants by providing lcrD in trans. A third mutant could not be complemented, and a plasmid carrying this mutation had a dominant negative effect over normal LcrD function. In the three mutants, the amount of mutant LcrD protein detectable in immunoblots was inversely related to the amount of complementation. Taken together, these data indicate that LcrD function involves the interaction of LcrD with another molecule.